The Effect of Liquidity and Leverage on Profitability with Investment Opportunity Set as a Moderating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange 2018-2022 - Salsabilla, Al-ainna Havizha; Fitri, Fitri; Asrilsyak, Sharnuke (International Journal of Economic, Business & Applications, 2024)
This study aims to determine the effect of liquidity and leverage on profitability with the investment opportunity set as a moderating variable. The population in this study includes all Energy companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022, totaling 65 companies. The sampling technique used a purposive sampling method, resulting in 49 companies that met the criteria. Data analysis was conducted using Moderating Regression Analysis (MRA) with the SPSS application. The results of this study indicate that 1) there is a significant effect of liquidity on the profitability of Energy companies, 2) there is a significant effect of leverage on the profitability of Energy companies, 3) the investment opportunity set can significantly moderate the relationship between liquidity and profitability, and 4) the investment opportunity set can significantly moderate the relationship between leverage and profitability.